KONSTRUKSI SOSIAL REVOLUSI HIJAU DI ERA ORDE BARU - Wahyu Budi Nugroho (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2018)
This paper seeks to examine the application and implications of the GreenRevolution in the country through the perspective of social construction Mary E.Pettenger. In her analysis, the perspective of Pettenger's social construction involvesthe dimensions of power, knowledge, social norms, and discourse or discourse. InIndonesia, the Green Revolution is better known as